2020
DOI: 10.1016/j.jamda.2019.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Specific Nutritional Biomarker Profiles in Mild Cognitive Impairment and Subjective Cognitive Decline Are Associated With Clinical Progression: The NUDAD Project

Abstract: Objectives: Nutritional insufficiencies have been associated with cognitive impairment. Understanding whether nutritional biomarker levels are associated with clinical progression could help to design dietary intervention trials. This longitudinal study examined a panel of nutritional biomarkers in relation to clinical progression in patients with subjective cognitive decline (SCD) or mild cognitive impairment (MCI). Design, setting and participants: We included 299 patients without dementia (n ¼ 149 SCD; age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 50 publications
2
17
1
1
Order By: Relevance
“…Additionally, in a combined analysis of predementia stages in our prospective and retrospective cohort, higher HDL cholesterol levels and lower CSF SAM and SAH levels in MCI were associated with clinical progression. The role of HDL cholesterol levels in AD is inconclusive 17,38 . One explanation for our findings could be that HDL is dysfunctional in AD, as also reported for type 2 diabetes and coronary heart disease, resulting in impaired protective effects while HDL cholesterol levels remain normal 39 .…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Additionally, in a combined analysis of predementia stages in our prospective and retrospective cohort, higher HDL cholesterol levels and lower CSF SAM and SAH levels in MCI were associated with clinical progression. The role of HDL cholesterol levels in AD is inconclusive 17,38 . One explanation for our findings could be that HDL is dysfunctional in AD, as also reported for type 2 diabetes and coronary heart disease, resulting in impaired protective effects while HDL cholesterol levels remain normal 39 .…”
Section: Discussionmentioning
confidence: 52%
“…A previous cross‐sectional study showed that lower levels of several nutritional biomarkers are already prevalent in patients with MCI 16 . In addition, in a retrospective study of patients with subjective cognitive decline (SCD) and MCI, we found modest associations between higher levels of high‐density lipoprotein (HDL) cholesterol and lower levels of CSF S‐adenosylmethionine (SAM) and clinical progression 17 . The role of nutritional biomarkers across the complete cognitive spectrum of AD remains, however, largely unknown.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…S‐adenosylmethionine (SAM), a natural compound produced in homocysteine metabolism in the human body, is the primary methyl donor and the precursor of glutathione. In mild cognitive impairment (MCI) with putative early AD pathology, SAM in the CSF was decreased 43,44 . SAM level is decreased in the brain of AD patients 45 …”
Section: Csf Oxidative Stress Markers In Ad In Vivomentioning
confidence: 99%
“…В ранее упомянутом исследовании 45 and Up Study [26] была выявлена ассоциация между СКС и гиперхолестеринемией. В другой работе [54] высокий уровень липопротеинов высокой плотности был связан с прогрессированием СКС.…”
unclassified